Correlation between discharge and water quality – case study Nišava River (Serbia) - Leščešen, Igor; Pavić, Dragoslav; Dolinaj, Dragan (Geographica Pannonica, 2018)
The water quality and river discharges were surveyed at two sites in Nišava River basin (Dimitrovgradand Niš) with complete data series for the ten-year period (2005–2014). For these stations SWQI wascalculated and correlation analysis was applied. The index value is dimensionless and varies between0 and 100 (best quality) It is derived from numerous physical, chemical, biological and microbiologicalparameters. At Niš station average annual value of SWQI is 78 (good) with a clear decrease trend overa ten-year period. On the other side, on Dimitrovgrad station, average annual SWQI is 89 (very good)with a clear positive trend. Goal of this paper was to determine if there is a correlation between riverdischarge and values of SWQI. Results of the Pearson correlation test between SWQI and daily dischargevalues for Dimitrovgrad station show a moderate linear relation was observed, r= -0.287, p =0.002. On Niš station same test has shown that there is no statistically significant relation between dischargeand water quality (r=0.103 p= 0.297). This study has shown that the correlation between SWQIand discharge is weak or not present at all at the investigated river.